(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Motives control the process of reading and learning, determine the content and essence of education along with the acquisition of activity. Therefore, in the process of education of students, educational motivations and comprehensive motivations are of great importance in the formation of a well-rounded person, a mature qualified staff.